2005
DOI: 10.1152/ajpregu.00590.2004
|View full text |Cite
|
Sign up to set email alerts
|

Food entrainment modifies the c-Fos expression pattern in brain stem nuclei of rats

Abstract: When food is restricted to a few hours daily, animals increase their locomotor activity 2-3 h before food access, which has been termed food anticipatory activity. Food entrainment has been linked to the expression of a circadian food-entrained oscillator (FEO) and the anatomic substrate of this oscillator seems to depend on diverse neural systems and peripheral organs. Previously, we have described a differential involvement of hypothalamic nuclei in the food-entrained process. For the food entrainment pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 39 publications
8
28
0
Order By: Relevance
“…Rhythmic expression of mPer1 and mPer2 in the NTS͞DMV͞AP area of the brainstem under RF is consistent with a recent report showing a feeding-dependent up-regulation of c-Fos expression under RF in the NTS, DMV, and AP (27). The NTS is a relay nucleus for visceral and gustatory sensory afferents, and it has also been suggested as a site of integration for visceral autonomic and sensory responses (28).…”
Section: Discussionsupporting
confidence: 91%
“…Rhythmic expression of mPer1 and mPer2 in the NTS͞DMV͞AP area of the brainstem under RF is consistent with a recent report showing a feeding-dependent up-regulation of c-Fos expression under RF in the NTS, DMV, and AP (27). The NTS is a relay nucleus for visceral and gustatory sensory afferents, and it has also been suggested as a site of integration for visceral autonomic and sensory responses (28).…”
Section: Discussionsupporting
confidence: 91%
“…In the PVN, it is noteworthy that the postprandial expression of Per2 coincides with a specific induction of c-fos mRNA and protein in the PVN Poulin & Timofeeva, 2008). This meal-induced pattern may be the response to digestive processes, as it has been observed in other relay structures providing input signals elicited by feeding to the brain (Ángeles-Castellanos et al, 2005;Mieda et al, 2006). Based on c-FOS activity, the VMH has also been proposed as the initiating structure for anticipatory activity (Ribeiro et al, 2007); in the present study, no significant changes of clock genes were observed in RFS rats.…”
Section: Discussionmentioning
confidence: 60%
“…In the brain of rats exposed to RFS, daily patterns of c-FOS expression are elicited or phase changed in hypothalamic and brain stem regions involved in mediating metabolic and arousal signals to the rest of the brain (Ángeles-Castellanos et al, , 2005Gooley et al, 2006;Meynard et al, 2005). Also, corticolimbic structures involved in hedonic and motivational processes exhibit food-entrained patterns of c-FOS expression Mendoza et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it is important to report that the DMH receives projections from the subfornical organ (Thompson & Swanson, 1998). Many brain areas are entrained by, or respond to, food availability (Ángeles-Castellanos et al, , 2005(Ángeles-Castellanos et al, , 2007Lamont et al, 2005a;Mieda et al, 2006;Poulin & Timofeeva, 2008;Verwey et al, 2007;Waddington Lamont et al, 2007;Wakamatsu et al, 2001). If brain regions responsible for behavioral expression are activated by ghrelin when it increases before mealtime during temporal food restriction, it would elicit the anticipatory behaviors observed during food entrainment.…”
Section: Ghrelinmentioning
confidence: 99%